A Short Note on the Tsergo Ri Landslide, Langtang Himal, Nepal - Weidinger, J. T.; Schramm, J. M. (Journal of Nepal Geological Society, 1995)
The large-scale mass movement at Tsergo-Ri (Langtang valley) in north-central Nepal was mapped in detail and an engineering geological map was prepared. Five different phases of displacement, deposition and erosion of the landslide are reconstructed. The present morphology of the area is largely the result of the above movement.